Exploring the Impact of Parent Gathering Programs on Cultivating Religious Character in Early Childhood: A Case Study - Utari, Sindy Mey Dwi; Arifin, Imron; Dian Putra, Yudithia (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study aims to investigate the positive impact of the parent gathering program implemented at TKIT Baitul Izzah Nganjuk on building children's religious character. The motivation for this study stems from the prevalent crisis in the country involving children, characterized by increasing violence, crime, and poor habits. Addressing these issues, the study explores the necessity of implementing a collaborative program between schools and parents to foster children's religious character. Design/methods/approach – The study was conducted at TKIT Baitul Izzah Nganjuk using a qualitative research method presented in a narrative format. Data collection comprised observation, interviews, and documentation. Data analysis was performed using the Miles and Huberman model. Findings – The study revealed that the parent gathering program included three main components: workshops, socialization, and evaluation. The religious character education implemented encompassed routine activities, periodic activities, and teaching and learning activities. The program's benefits were observed in shaping effective parenting patterns and fostering in children an awareness of worship, faith, and good behavior. Research implications/limitations – This research recognizes its scope limitations, focusing solely on the parent gathering program for new students. Practical implications – The findings indicate that the parent gathering program is a valuable tool for building the religious character of early childhood, necessitating cooperation between the school and parents. Originality/value – The implementation of the parent gathering program has shown effectiveness in nurturing religious character from an early age. Paper type Case study